GENERALIZED α-ψ-φ-F-CONTRACTIVE MAPPINGS IN QUASI-b-METRIC-LIKE SPACES - Kadwin, J. G.; Raj, S. I.; Jiny, D.M. (Journal of Nonlinear Analysis and Optimization: Theory & Applications (JNAO), 2024)
In this paper, we introduce some new generalized mappings in quasi-b-metric-like spaces and establish some fixed point theorems with concrete examples. Our results generalize fixed point results in the literature.